2020
DOI: 10.1093/jrs/feaa034
|View full text |Cite
|
Sign up to set email alerts
|

Double-edged risk: unaccompanied minor refugees (UMRs) in Sweden and their search for safety

Abstract: Many unaccompanied minor refugees (UMRs) arrived in Sweden with the mass exodus of refugees who fled to the EU in 2015. UMRs are individuals who are under 18 years of age, outside their country of origin and separated from legal care-givers (Separated Children in Europe Programme 2004). In 2016, Swedish public opinion of asylum seekers began to shift from sympathy to fear (Kärrman 2015; Herz 2018) and Sweden implemented policies restricting UMRs’ rights. It was at this pivotal moment that we interviewed UMRs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Minors under the age of 18 now represent above one-third of all asylum-seekers worldwide, with 153,000 reported as unaccompanied in 2019 [ 1 ]. There are also age- and gender-specific threats involved, including forced recruitment, sexual exploitation and being forced to leave parents [ 2 4 ]. In 2019, one-third of asylum applicants to Europe were minors aged less than 18 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Minors under the age of 18 now represent above one-third of all asylum-seekers worldwide, with 153,000 reported as unaccompanied in 2019 [ 1 ]. There are also age- and gender-specific threats involved, including forced recruitment, sexual exploitation and being forced to leave parents [ 2 4 ]. In 2019, one-third of asylum applicants to Europe were minors aged less than 18 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the participants are a heterogeneous group with different ages, stages in life, life circumstances, levels of education, and lengths of stay in Sweden; therefore, they might have various understandings of SRH and different experiences of SRH services. Despite this heterogeneity, young migrants coming from the Middle East are often portrayed by part of the Swedish society and media as a ‘homogeneous’ group characterised as sexual perpetrators and a threat to Swedish society, culture, and values ( Herz, 2019 ; Horning et al., 2020 ). We acknowledge that focusing on them as a group under the ‘common’ ground of sharing a language risks reinforcing the idea of a ‘shared identity’ that downplays the heterogeneity of this group and risks stereotypification.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond a number of studies focusing on health policy, and service provision (e.g. Derluyn et al, 2007;Kohli, 2006;Wimelius, et al, 2017), a growing body of research takes a critical perspective by analysing concepts such as racialization, home, belonging, masculinities, safety and deservingness (Hedlund, 2015;Herz, 2019;Horning, et al, 2020;Stretmo, 2014;Wernesjö, 2015Wernesjö, , 2020. Among other issues, this research has demonstrated how 'unaccompanied minors' are positioned as either vulnerable victims/or potential threats, but also how the children and youth themselves use, negotiate and resist such subject positions (Herz, 2019;Kohli, 2006;Stretmo, 2014;Wernesjö, 2020).…”
Section: Swedish Migration Policy and Receptionmentioning
confidence: 99%
“…Being positioned as the 'other' and/or a stranger has multiple consequences for subjects, such as being exoticized, excluded, and/or held responsible for failed integration. In addition, the 'other' may be positioned as a victim in need of help, or as a potential threat, with the risk of being stopped, detained or even killed (Ahmed, 2000;Hällgren, 2005;Horning et al, 2020).…”
Section: Conceptual Framework: Politics Of Belonging and The Strangermentioning
confidence: 99%
See 1 more Smart Citation